Mathematical Problem-Solving Behaviors of the Routine Solver - Mairing, Jackson Pasini (UPI Press, 2020)
The research refined the theories of students’ characteristics in solving mathematical problems and constructed a holistic understanding of their problem-solving behaviors. It aimed at describing the problem-solving behaviors of a routine problem solver. The routine bridged the gap between the expert and the novice. This research used a qualitative approach which was carried out in six stages. The research participant was Rina (female, pseudonym), one of the 11th-grade students from one of the high schools in Palangka Raya City, Central Kalimantan, Indonesia. The selection of the participant was based on certain criteria. The instruments were three mathematics problems and semi-structured interviews. The trustworthiness of the research was fulfilled through credibility, dependability, and transferability checking. The results showed that the routine could understand problems and was able to identify the known and the target. The routine only focused on developing a plan which was based on a lack of concepts, limited previous experiences, or limited strategies. Problem-solving behaviors of the routine were between the expert and the novice.